PERJANJIAN KERJASAMA DALAM BIDANG PENGKARYAAN DAN JASA TENAGA KERJA ANTARA PT. SINAR JAYA PURA ABADI DAN PT. ASIANFAST MARINE INDUSTRIES - R Juli Moertiono (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2019)
The outsourcing system uses a cooperation agreement of differences in interests which are brought through an agreement. The cooperative relationship between outsourcing companies and companies using outsourcing services is certainly tied to a written agreement. PT. Asianfast Marine Industries intends to use the services of a security workforce, who is ready to meet the need for labor services and to carry out the business activities of the company, from a labor service provider company, PT. Sinar Jaya Pura Abadi. The cooperation agreement between PT. Sinar Jaya Pura Abadi and PT. Asianfast Marine Industries which intends to employ security workers contains 19 (nineteen) Articles i.e. purpose and objectives, general provisions, rights and obligations of the parties, duties and responsibilities of first parties, provisions concerning labor, wages and payment method, responsibility and compensation, work safety, dispute resolution. The rights and obligations of the company and the employed workforce are that PT. Asianfast Marine Industries is obliged to carry out the contents of the cooperation agreement which covers the employed workforce, and legal protection for the labor in the event of default.Keyword: Agreement, Cooperation, Labor